Factors that influence consumers' participation in EBPP: case study with Kuching Water Board / Nancy Haji Hossen - Haji Hossen, Nancy (2004)
Electronic bill presentment and payment (or EBPP) is defines as a technology solution that allows billers to present their bills electronically to consumers or companies which enables these parties to initiate electronic payment. EBPP consist of two components: i. Electronic bill presentment which focused on electronically transmitting bills from billers to consumers and ii. Electronic bill payment, which focus on electronically transmitting payment from consumers to billers through the financial institutions via the Internet. (Value Positions of Financial Institutions in EBPP, Page 1 - Dr Aiea M Fairchild) EBPP is relevant to corporation in the financial services, telecommunications and utilities like Kuching Water Boards (KWB). These corporations usually produce hundreds of thousand of bills every month. The main objective of introducing EBPP is for consumers’ convenience and time saving to settle their bills. For billers, EBPP helps to improve the efficiency and effectiveness in the workflow besides being cost effective to the organization. Kuching Water Board is among the utilities corporation that participate in EBPP service.